Uma abordagem crítica sobre a ressocialização na pena privativa de liberdade e nas penas alternativas - Façanha, Leonardo Lima (2009)
Analyze the theme of ressocialization in the current model of segregation of the criminal taking into account the problems and opportunities of the system carceral Brazilian, discussing the bankruptcy imprisonment and tackling the ressocialization aspect in alternative sentences. The debates on the ressocialization in prison and alternative sentences are associated, in good part, to the problems presented by prison systems. Reflect on the limits and possibilities of ressocialization within the framework of deprivation of liberty in Brazil and, in addition, to discuss the ressocialization in alternative sentences pointing a way to crisis penitentiary installed in country. The penalty involving deprivation of freedom as criminal response par excellence is deeply rooted in Brazilian cultural life, for the majority, the punishment can only be effective with arrest. . Prioritizing the discussion of the problem of criminality, focusing on theories studying the phenomenon of crime and its repercussions on social environment, analyzing the appearance of deprivation of freedom as principal answer of the State crime, researching constitutional law of Brazilian concerning implementation of the sentence, understanding how the ressocialization is inserted in the context of public policies criminal and identifying the real way of this institute in prisons Brazilians.